(3HOjYjI YR GdOjf GdehUdis - (3Ydj Hf GdMSjf Hf Ydj GdehUdj ; YR GdOjf,(B789 (3g`s ((3YeQ CfSi Hf eMeO OjH GdUbYGf GdHjQhJi s)
(3ChdgG (B:s
(3aMi SdekG hSd eGQcHJ HPG bO CWdbJ CeGe GdMi Yf Cee s
(3BNQgG (B:s
(3aGLYd dg eNdUkG ef bHM RdJg ai MSf eaJJM efg heNJJe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B91 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B75s
Keywords: (3GdHdGZIs